Cellular Detection of Hydrazine as Isoniazid Metabolite by a New Turn‐On Fluorescent Probe: Synthesis, Live Cell Imaging and In Vitro Toxicity Studies. Issue 45 (4th December 2018) - Banerji, Biswadip; K, Chandrasekhar; Chatterjee, Satadru; Killi, Sunil Kumar; Prodhan, Chandraday; Chaudhuri, Keya
Abstract: A new turn‐on fluorescent probe 2‐((pyren‐3‐yl) methyl) isoindoline‐1, 3‐dione was synthesized in a single step, high yielding reaction to detect hydrazine in solution. This ligand is highly sensitive to detect hydrazine in micromolar (1.1 μM) concentration in solution. It has high selectivity towards hydrazine compared to other analytes. Different biophysical experiments like hydrazine screening from both tap water and distilled water, vapour phase detection, anti‐interference studies with different analytes also corroborate the phenomenon of selective detection of hydrazine by our ligand. NMR titration and mass spectrum established the mechanism of hydrazine sensing. In addition, the probe was successfully used to trap exogenously added hydrazine inside the cell, which was further utilized to study insitu hydrazine released from an anti‐tubercular drug Isoniazid (INH), after its metabolism. Abstract : A new turn on fluorescent probe was synthesized in a single step reaction in good yield to detect hydrazine in solution. It has high selectivity towards hydrazine compared to other relevant analytes. The probe was shown to detect exogenously added hydrazine inside the cell efficiently, which was further explored to study insitu hydrazine released from Isoniazid (INH), after its metabolism. Thus it was used as a protective reagent against hepatotoxicity induced by the release of hydrazine from the drug INH.